2023
DOI: 10.29076/issn.2528-7737vol16iss42.2023pp102-115p
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo son las empresas excelentes para trabajar en España durante la pandemia del COVID-19?

Abstract: Las empresas más atractivas para trabajar son de especial interés porque suponen una importante relevancia en el mercado de trabajo y la sociedad. El objetivo de este artículo es analizar las empresas más atractivas del mercado laboral en España que permanecen todos los años en el ranking publicado por la Revista Actualidad Económica, durante el periodo 2013-2020. Se investiga la excelencia laboral de estas empresas durante el duro comienzo de la pandemia COVID-19, además de caracterizarlas con indicadores tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Indeed, in Table 4 it was observed that the companies in the ranking with greater female presence are better positioned in the ranking, according to Ferreiro-Seoane et al (2021) and Ferreiro-Seoane et al (2023b). This fact is reflected mostly in the Work Environment item where they express more intensity in favour of companies managed by women, but this fact does not seem to effectively promote this social objective.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, in Table 4 it was observed that the companies in the ranking with greater female presence are better positioned in the ranking, according to Ferreiro-Seoane et al (2021) and Ferreiro-Seoane et al (2023b). This fact is reflected mostly in the Work Environment item where they express more intensity in favour of companies managed by women, but this fact does not seem to effectively promote this social objective.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in Table 4 it was observed that the companies in the ranking with greater female presence are better positioned in the ranking, according to Ferreiro‐Seoane et al. (2021) and Ferreiro-Seoane et al. (2023b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation